Managing the Family Firm: Evidence from CEOs at Work - Bandiera, Oriana; Lemos, Renata; Prat, Andrea; Sadun, Raffaella (Review of Financial Studies, 2018)
We present evidence on the labor supply of CEOs and on whether family and professional CEOs differ on this dimension. We do so through a new survey instrument that allows us to codify CEOs’ diaries in a detailed and comparable fashion and to build a bottom-up measure of CEO labor supply. The comparison of 1,114 family and professional CEOs reveals that family CEOs work 9% fewer hours relative to professional CEOs. Hours worked are positively correlated with firm performance, and differences between family and non-family CEOs account for approximately 18% of the performance gap between family and non-family firms. We investigate the sources of the differences in CEO labor supply across governance types by exploiting firm and industry heterogeneity and quasi-exogenous meteorological and sport events. The evidence suggests that family CEOs value—or can pursue—leisure activities relatively more than professional CEOs. Layperson summary